Candle light-style OLEDs with benzochalcogenadiazoles cores. (February 2021) - Korshunov, Vladislav M.; Chmovzh, Timofey N.; Golovanov, Ivan S.; Knyazeva, Ekaterina A.; Mikhalchenko, Lyudmila V.; Saifutyarov, Rasim S.; Avetisov, Igor C.; Woollins, J. Derek; Taydakov, Ilya V.; Rakitin, Oleg A.
Abstract: Fluorescent D-A 1 -π-A 2 dyes containing the 9-hexyl-9 H -carbazole electron-donor unit and 2, 1, 3-benzochalcogenadiazoles as electron-withdrawing, were synthesized. These dyes displayed high luminescence quantum yields up to 20% in the solid phase and 80% in solutions. A series of ClsOLEDs with high luminance up to 6256 cd/m 2 and low color temperature (1800–1900 K) based on these dyes were constructed. The electroluminescence color temperature of the fabricated OLEDs is independent of the operating voltage making these compounds potentially very useful for night time illumination. It was shown that the aggregation process of the investigated dyes led to the formation of planar crystalline structures. Scanning electron microscopy (SEM) and fluorescence lifetime imaging (FLIM) experiments, showed that luminescence quenching caused by interactions between aggregates of different sizes takes place. Spectroscopic studies were supported by Density Functional Theory (DFT) and Time Dependent Density Functional Theory (TD-DFT) calculations. As a result, we elucidated that replacement of [1, 2, 5]chalcogenadiazolo[3, 4- c ]pyridines by 2, 1, 3-benzochalcogenadiazoles led to a substantial improvement in intramolecular charge transfer (ICT) from the donor to acceptor units due to favourable distortion of the excited state geometry. Graphical abstract: Image 1